2009
DOI: 10.1016/j.ecoleng.2008.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Substrate effect on bacterial communities from constructed wetlands planted with Typha latifolia treating industrial wastewater

Abstract: Constructed wetlands (CWs) have been recognized as being able to effectively treat wastewater from municipal and industrial sources. This study focused on the effect of different substrates and long-term operation of horizontal subsurface flow CWs treating tannery wastewater on the bacterial communities. The CWs were planted with Typha latifolia in three types of substrate: two units with different types of expanded clay aggregates and one unit with fine gravel. Another unit with expanded clay was left unveget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 22 publications
3
41
0
1
Order By: Relevance
“…These properties will influence the development of the biota which the substrate provides support for. In fact, it has been observed that some particular materials seem to be preferable media for some plant species and microorganisms strains [81][82][83]90]. On the other hand, the development and activity of the biotic elements may over time affect and modify the support matrix characteristics.…”
Section: Support Matrixmentioning
confidence: 99%
See 4 more Smart Citations
“…These properties will influence the development of the biota which the substrate provides support for. In fact, it has been observed that some particular materials seem to be preferable media for some plant species and microorganisms strains [81][82][83]90]. On the other hand, the development and activity of the biotic elements may over time affect and modify the support matrix characteristics.…”
Section: Support Matrixmentioning
confidence: 99%
“…In the past, much of the design of CWS has been done with little knowledge of (or consideration for) the roles played by each component and how their effects could be enhanced and optimized. However, over the most recent years some accumulated knowledge has been increasingly applied in the construction and operation of new systems, which results in a much greater variety of plant species, support matrix materials and constructed wetland designs being seen, studied and introduced in newly set up CWS [35,42,43,58,60,[73][74][75][76][77][78][79][80][81][82][83][84][85]. The goals of the target contaminants to remove in those CWS have also become increasingly more ambitious.…”
Section: Removal Of Organic Xenobiotics In Cwsmentioning
confidence: 99%
See 3 more Smart Citations